THE EFFECT OF DISCOVERY LEARNING STRATEGY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMPN 1 SUNGAI MANDAU IN COMPREHENDING NARRATIVE TEXTS - Sari, Putri Nilam; Purwanti, Indah Tri; Erni, Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The research aims to investigate the effect of Discovery Learning Strategy on the ability of the second year students of SMPN 1 Sungai Mandau in comprehending narrative texts. In conducting the research, pre- experimental research with one group pre-test post- test design was used. The sample of this research was the students of class VIIIc which consisted of 29 students. The pre- test was administered before the treatment. After the treatment was applied for four meetings using Discovery Learning Strategy, a post-test was administered. The data were analyzed using the t-test formula. From the calculation, the writer found that the value of t-test was 2.311 while the t-table was 2.048. Since the t-test value was larger than that of t-table, the alternative hypothesis of this research was accepted and null hypothesis was rejected. It means that there was a significant effect of Discovery Learning Strategy on the ability of the second year students of SMPN 1 Sungai Mandau in comprehending narrative texts.Key Words: Reading,Reading Comprehension, Discovery Learning Strategy, Narrative Text